Measuring Physical Activity in Free-Living Conditions—Comparison of Three Accelerometry-Based Methods - Leinonen, Anna-Maiju; Ahola, Riikka; Kulmala, Janne; Hakonen, Harto; Vähä-Ypyä, Henri; Herzig, Karl-Heinz; Auvinen, Juha; Keinänen-Kiukaanniemi, Sirkka; Sievänen, Harri; Tammelin, Tuija H.; Korpelainen, Raija; Jämsä, Timo (Frontiers in Physiology, 2017)
We examined the agreement in time spent on different physical activity (PA) levels using 1) mean amplitude deviation (MAD) of raw acceleration from the hip, 2) wrist-worn Polar Active, and 3) hip-worn Actigraph counts using Freedson’s cut-points among adults under free-living conditions. PA was measured in 41 volunteers (mean age 47.6 years) for 14 days. Two MET-based threshold sets were used for MAD and Polar Active for sedentary time (ST) and time spent in light (LPA), moderate (MPA), and vigorous (VPA) PA. Actigraph counts were divided into PA classes, ≤100 counts/min for ST and Freedson’s cut-points for LPA, MPA, and VPA. Analysis criteria were simultaneous use of devices for at least 4 days of >500 min/d. The between-method differences were analyzed using a repeated measures analysis of variance test. Bland-Altman plots and ROC graphs were also employed. Valid data were available from 27 participants. Polar Active produced the highest amount of VPA with both thresholds (≥5 MET and ≥6 MET; mean difference 17.9–30.9 min/d, P<0.001). With the threshold 3–6 MET for MPA, Polar Active indicated 19.2 min/d more than MAD (95%CI 5.8–32.6) and 51.0 min/d more than Actigraph (95%CI 36.7–65.2). The results did not differ with 3.5–5 MET for MPA (F(1.44,37.43)=1.92, P=0.170). MAD and Actigraph were closest to each other for ST with the threshold <1.5 MET (mean difference 22.2 min/d, 95%CI 7.1–37.3). With the threshold <2 MET, Polar Active and Actigraph provided similar results (mean difference 7.0 min/d, 95%CI -17.8–31.7). Moderate to high agreement (area under the ROC curve 0.806 to 0.963) was found between the methods for the fulfillment of the recommendation for daily moderate-to-vigorous PA of 60 minutes. In free-living conditions the agreement between MAD, Polar Active, and Actigraph for measuring time spent on different activity levels in adults was dependent on the activity thresholds used and PA intensity. ROC analyses showed moderate to high agreement for the fulfillment of the recommendation for daily MVPA. Without additional statistical adjustment, these methods cannot be used interchangeably when measuring daily PA, but any of the methods can be used to identify persons with insufficient daily amount of MVPA.